PENDIDIKAN KRISTEN DALAM KELUARGA DALAM UPAYA MEMBANGUN KARAKTER ANAK GENERASI Z - Nurmaliel Toding K; Armila, Yumita Selvi Rombe Payung, Seprina Pilo, Asriani Ra’pean (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research aims to analyze the role of Christian education within the family environment as a crucial factor in shaping the character of Generation Z children. Generation Z, born from the late 1990s to the early 2010s, is a demographic that has grown up in the era of information technology, facing unique challenges in building strong and healthy moral character. Christian education is considered one of the approaches that can provide a solid moral foundation in dealing with various pressures and temptations in their surroundings. The research methodology employs a qualitative approach with data collection techniques, carried out through thematic analysis to identify patterns and themes emerging from participant narratives. The results of this research are expected to provide deep insights into how Christian education within the family can influence the formation of Generation Z children's character. These findings are anticipated to offer concrete suggestions for parents, churches, and religious education institutions in developing more effective and relevant Christian education strategies for Generation Z children